Subtitle Translation Strategy: Cross-Cultural Translation of Japanese Kuso's Profanity Words - Murniati Br Barus (Tradition and Modernity of Humanity, 2024)
The translation of subtitles in an animation is crucial for understanding the message sent to the viewer. The objective of this research is to determine effective methods for translating Japanese kuso profanities into Indonesian. The utilized data is sourced from Hakyu anime, which prominently features a substantial amount of obscenity, particularly the term "kuso". The data was gathered through the process of observing films and recording instances of just swearing. Subsequently, it is categorized based on its classification. The data analysis reveals that three procedures are employed in the translation of kuso's profane words into Indonesian. Kuso's profane terms are translated as 'excrement,' 'condemn,' 'contemptible person,' and even the intensifier 'very.' The study findings indicate that kuso profanity words are used in informal contexts, directed not only toward the listener but also towards oneself.